(untitled) (Medical Forum Monthly, 2024)
Objective: Thyroid hypo function is known to cause renal impairment. The present Cross-Sectional study was conducted to investigate the effects of thyroid hypo function on the Serum Biochemical Markers (SBM) of Renal Function (RF) in Non-pregnant hypothyroid women. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Khyber Teaching Hospital (KTH) a tertiary care hospital in KhyberPakhtun Khwa province of Northern Pakistan from 01 March 2014 to 31 March 2015 Materials and Methods: Thyroid profile status (T3, T4 and TSH levels) was determined for the selected 150 patients. On the basis of Thyroid profile, patients were divided into three groups as Normal (N) (n=54), Sub-clinically hypothyroid (Sh) (n=48) and overtly hypothyroid (Oh) (n=48). Biochemical analysis for Serum Creatinine (S.C) and Serum Urea (S.U) were conducted in all the patients and the data was analyzed statistically, using SPSS version 21. Results: A minor decrease in the serum creatinin level in the Oh (1.10mg/dl) and Sh group (1.18 mg/dl) was found as compared to N group (1.47mg/ dl). Serum urea was found to be slightly decreased in the Sh group (23.22 mg/dl) as compared to N group (32.60mg/dl) and Oh group (30.11mg/dl). A very significant positive correlation was found between Serum creatinine and T3 in the Sh group (p= 0.005) and significant negative correlation with T3 in the N group (p= 0.05).Urea was significantly negatively correlated with TSH in Sh group (p= 0.05). Conclusion: Hypothyroidism may not affect renal functions in non-pregnant women in Northern areas of Pakistan.